Employee Performance Evaluation Using A New Preferential Voting Process - Mehdi Soltanifar; Seyed Abdullah Heidariyeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: This study aimed to determine the comprehensive performance evaluation criteria to improve employees' performance evaluation system using a new data envelopment analysis model based on 360-degree evaluation for employee ranking. Methodology: This study first identified performance evaluation criteria by studying the research background. Questionnaires designed based on the opinions of twenty-five organization staff, three senior managers, ten professors with university experience, and ten active and selected university students (48 people in a 360-degree structure) are completed. Then, employee ranking was performed using A new model of designed data envelopment analysis. Twelve performance evaluation indicators extracted from the research background by experts in four categories with the titles of service compensation system in the first category; Job security, perceived organizational justice, perceived organizational support, and physical working conditions in the second category; Job characteristics, job clarity and ability of employees in the third category and job feedback, job stress, organizational citizen behaviour and motivation in the fourth category were ranked and documented using a linear optimization model based on the goal programming and policy. Data envelopment analysis resulted in a complete ranking for the staff of a university unit with 25 staff members. Findings: Interpretation and analysis of structured results obtained using a data envelopment analysis policy based on 360-degree evaluation can be the basis for improving human resources and continuing periodic evaluation to enhance employee performance continuously. Originality/Value: The present study can help their evaluations by using various indicators comprehensively and a 360-degree approach and considering the external and internal challenges of the organization.